Very early diagnosis of chest pain by point-of-care testing: comparison of the diagnostic efficiency of a panel of cardiac biomarkers compared with troponin measurement alone in the RATPAC trial. Issue 4 (10th November 2011) - Collinson, Paul; Goodacre, Steve; Gaze, David; Gray, Alasdair
Abstract : Objective: To assess the impact of triple marker testing on patient management and the diagnostic efficiencies of different biomarker strategies examined. Design: A prospective randomised trial of triple marker testing by point-of-care testing (POCT); the Randomised Assessment of Panel Assay of Cardiac markers (RATPAC) study. Setting: Six emergency departments. Patients: Low-risk patients presenting with chest pain to diagnostic assessment with a cardiac panel measured by POCT or to diagnosis when biomarker measurement was based on central laboratory testing. Interventions: 1125 patients were randomly assigned to POCT measurement of the triple marker panel of cardiac troponin I (cTnI), myoglobin and the MB isoenzyme of creatine kinase (CK-MB) on admission and 90 min from admission. Main Outcome Measures: Myocardial infarction (MI) was defined by the universal definition of MI. The following diagnostic strategies were compared by receiver operator characteristic (ROC) curve analysis and comparison of area under the curve (AUC): individual marker values, change (Δ) in CK-MB and myoglobin and the combination of presentation or 90 min value plus Δ value. Results: Admission sample measurement of cTnI was the most diagnostically efficient AUC 0.96 (0.93–0.98) with areas under the ROC curve statistically significantly greater than CK-MB 0.85 (0.80–0.90) and myoglobin 0.75 (0.68–0.81). At 90 min cTnI measurement had the highest AUC 0.95 (0.87–1.00) but was statistically significantly different only from Δmyoglobin and ΔCK-MB. Conclusion: Measurement of cTnI alone is sufficient for diagnosis. Measurement of a marker panel does not facilitate diagnosis.